The Impact of Gastroesophageal Reflux Disease (GERD) on Pharyngeal Mucosal Changes: A Case-Control Study in Indonesia - Dedi Sucipto; Nurul Hanifah; Vidhya Sathyakirti; Louisa Istarini; Syaifudin Syaifudin (Sriwijaya Journal of Otorhinolaryngology, 2024)
Introduction: Gastroesophageal reflux disease (GERD) is a prevalent digestive disorder with potential extra-esophageal manifestations, including laryngopharyngeal reflux (LPR). LPR can lead to various pharyngeal mucosal changes, impacting voice quality and overall well-being. This study aimed to investigate the association between GERD and pharyngeal mucosal changes in a population in Indonesia. Methods: A case-control study was conducted at a tertiary hospital in Indonesia, involving 100 participants diagnosed with GERD (cases) and 100 participants without GERD (controls). All participants underwent a comprehensive ear, nose, and throat (ENT) examination, including flexible nasopharyngoscopy, to assess pharyngeal mucosal changes. The Reflux Symptom Index (RSI) questionnaire was used to evaluate the severity of reflux symptoms. Data were analyzed using SPSS software, employing chi-square and logistic regression analyses to determine the association between GERD and pharyngeal mucosal changes. Results: The study found a significantly higher prevalence of pharyngeal mucosal changes in the GERD group compared to the control group (78% vs. 22%, p<0.001). Erythema, edema, and posterior pharyngeal wall cobblestoning were the most common findings in GERD patients. The severity of reflux symptoms, as measured by the RSI, was positively correlated with the presence and severity of pharyngeal mucosal changes. Conclusion: GERD is significantly associated with pharyngeal mucosal changes in the Indonesian population studied. These findings underscore the importance of recognizing and managing LPR in patients with GERD to prevent potential complications and improve quality of life.